2015
DOI: 10.1111/desc.12314
|View full text |Cite
|
Sign up to set email alerts
|

What would Batman do? Self‐distancing improves executive function in young children

Abstract: This experimental research assessed the influence of graded levels of self-distancing - psychological distancing from one's egocentric perspective - on executive function (EF) in young children. Three- (n = 48) and 5-year-old (n = 48) children were randomly assigned to one of four manipulations of distance from the self (from proximal to distal: self-immersed, control, third person, and exemplar) on a comprehensive measure of EF. Performance increased as a function of self-distancing across age groups. Follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 38 publications
4
96
1
Order By: Relevance
“…In other research, executive function has recently been found to be positively and uniquely affected by fantastical pretend play (Thibodeau et al, 2016). Other work in this age group has shown that when 5-year-old children pretend to be a character (e.g., Batman), or to view themselves in a third person manner, they increase their executive function (White & Carlson, 2015) and…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In other research, executive function has recently been found to be positively and uniquely affected by fantastical pretend play (Thibodeau et al, 2016). Other work in this age group has shown that when 5-year-old children pretend to be a character (e.g., Batman), or to view themselves in a third person manner, they increase their executive function (White & Carlson, 2015) and…”
Section: Discussionmentioning
confidence: 78%
“…In other research, executive function has recently been found to be positively and uniquely affected by fantastical pretend play (Thibodeau et al., ). Other work in this age group has shown that when 5‐year‐old children pretend to be a character (e.g., Batman), or to view themselves in a third person manner, they increase their executive function (White & Carlson, ) and perseverance (White et al., ). Therefore, these results could have emerged because children in the DPPG group gained an ability to task switch, to distance themselves from emotionally charged situations, to see themselves as separated, and to control their reactions based on their distance from someone else's distress, rather than affecting emotional control directly.…”
Section: Discussionmentioning
confidence: 94%
“…One promising approach to increase accurate reasoning about the future is to manipulate psychological distance to observe whether children reason differently about a thirsty self's future compared with a thirsty other's future. Research examining the ability to mentally detach from one's own beliefs, desires, and circumstances to reason from a perspective different from one's own, known as psychological distancing, reports positive effects on children's and adults' future decision making in a number of future‐oriented domains (e.g., Kross & Grossmann, ; Lee & Atance, ; Prencipe & Zelazo, ; Pronin, Olivola, & Kennedy, ; White & Carlson, ; Ziegler & Tunney, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study which was conducted by R. White and S. Carlson (White & Carlson, 2016) confirmed the effectiveness of this approach as it examined the impact of performing EF assignments depending on the role that the child takes on itself (White, Carlson, 2016). The tasks were presented in three options: first, a traditional one, second, a situation where the child represented another child performing the task ("Where does John think this card belongs to?")…”
Section: Use Of Play Activities To Impact Executive Functions Developmentioning
confidence: 99%